(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Taking the recent publication of the Palaeohispanic onomas-ticon in the Hesperia Databank as a starting point, this work will focus on the following aspects: 1. description of the available sources for the study of Ibe-rian personal names; 2. criteria for the inclusion of names into the catalogue; 3. main features of an online onomastic corpus.